(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
De noche vienes (1979) by the Mexican writer, Elena Poniatowska, encompasses sixteen short stories, which ―from different paradigms― show men and women in a hostile context. This surrounding makes them to live alone. These short stories center on the necessity of reviewing the imposed forms pf social construct, questioning the ruling politics and morale in Mexico in the seventies, Poniatowska’s narrative is related to the possibility for literature to help to denounce traditional cultural construct that make up situations of marginality inmexican society. This work proposes an ideological reading of some of the stories of De noche vienes, in which female characters are portrayed trying to charge the imposed and prevailing patriarchal system.